Real-world data for the availability of pediatric medicines in Chinese hospitals: a multi-center survey and analysis - Ruan, Wen-Yi; Chen, Hui-Ying; Cai, He-Ping; Wang, Xiao-Ling; Zhao, Zhi-Gang (Frontiers in Pharmacology, 2024)
There is no information on the availability of pediatric medicines in China. To access the availability of different types of pediatric medicine and determine their ratio in medical institution drug catalogs. Based on drug instructions, the expert meeting method was used to divided pediatric medicines into five categories: child-specific medicine (CSM), co-use medicine for adults and children (CMAC), other pediatric medicine (OCM), off-label medicine use (OMU), and non-child medicine (NM). A total of 60 hospitals nationwide participated in this survey, including 20 children's hospitals (C-hosp), 14 maternal and child health care hospitals (MCHC-hosp), and 26 general hospitals (G-hosp). The average number of drug catalogs in G-hosp was significantly higher than those in C-hosp and MCHC-hosp. CSM accounted for 9.77% of C-hosp catalog, 7.12% of MCHC-hosp catalog, and 1% of G-hosp catalog. The availability rate of CMAC was 49.63% in C-hosp and 40.87% and 31% in MCHC-hosp and G-hosp, respectively. The proportion of OCM in the C-hosp (27.28%) was higher than that in the MCHC-hosp (13.4%) and G-hosp (5%). OMU occupied ratio in C-hosp, MCHC-hosp and G-hosp is not negligible, which was 12.06%, 8.7% and 10% respectively. The proportion of NM in the C-hosp was almost negligible, but was 29.91% and 53% in the MCHC-hosp and G-hosp, respectively. Compared to the CSM and CMAC listed in China, the share of CSM in C-hosp was close to 40%, which was much higher than that of G-hosp and MCHC-hosp. In contrast, the share of CMAC in G-hosp was nearly 30%, which was significantly higher than that in C-hosp and MCHC-hosp. Health insurance covers most of these five types of pediatric medicines, with the proportion of insured medicines reaching close to 80% in C-hosp and approximately 85% in MCHC-hosp and G-hosp. The availability of specific medicines suitable for use in children is generally low, and even the CSM in specialized hospitals such as C-hosp cannot meet the relatively high accessibility level of WHO evaluation standards. Policies and measures should be implemented to boost research and development of pediatric medicines, as well as supplement safety information lacking in instruction manuals.